Study of Profile on Juvenile criminals in Chennai - Siddharth.R1, V.Dekal2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Juvenile delinquency is a serious offence and it is detrimental for the social order in any country .There is a trend of increase in juvenile crimes world-over, with more and more involvement of the youth in violent crimes. Chennai shows similar trends of increasing rate of violent crimes committed by the juveniles. It is a very serious concern for the district and solutions to end the problem need to be sought very carefully. Indian legal system and judiciary has responded to these trends and has brought some amendments in the laws pertaining to juvenile justice in India [1]. This paper aims at looking at the causes of juvenile delinquency and explanations in Chennai for the year 2016. The analysis of statistical data available at the CBCID office crime branch indicates increasing involvement of the juveniles in heinous crimes. Observation homes, Shelter homes have been started by the government for the sake of such offenders then also the rate is continuously increasing day by day. For delinquent juvenile we can say that Prevention is better than cure juveniles should be protected from going to the wrong path.